Aplicación móvil Android para gestión de empleados, de bovinos e informes sobre la producción de leche de la hacienda Indonesia. (2022)
Currently, the livestock industry and international trade of Colombian milk production is growing, however, the lack of implementation of new technologies, infrastructure and individualism of entrepreneurs, prevents being level with countries such as the United States and Argentina. Likewise, with the rise of information technologies, it is essential that any organization in any business sector, in this case the agricultural sector, be at the service of and facilitate access to information and quick and accurate decision making.